Computational biomechanical modeling of fibrin networks and platelet-fiber network interactions. (June 2022) - Pancaldi, Francesco; Kim, Oleg V.; Weisel, John W.; Alber, Mark; Xu, Zhiliang
Abstract: Fibrin deformation and interaction of fibrin with other blood components play critical roles in hemostasis and thrombosis. In this review, computational and mathematical biomechanical models of fibrin network deformation and contraction at different spatio-temporal scales as well as challenges in developing and calibrating multiscale models are discussed. The long standing challenges include careful evaluation of the applicability of models to identify and test potential mechanisms of the biomechanical processes mediating interactions between platelets and fiber networks in blood clot stretching and contraction. Also, there is a need to use modeling approaches to determine how exactly structural and mechanical properties of major blood clot components can influence biomechanical responses of the entire clot subjected to external forces, such as blood flow or vessel wall deformations. Highlights: Multiscale models are needed to describe fibrin mechanics, deformation and contraction. Role of biomechanical interactions between platelets and fiber networks in blood clot stretching and contraction models. Local strain-stiffening and pairwise interactions of individual fibers contribute to mechanical responses of fibrin networks. Open problems and challenges: studing microscale mechanisms; multiscale model development, calibration and verification.